Precision medicine of aneurysmal subarachnoid hemorrhage, vasospasm and delayed cerebral ischemia. (1st November 2016) - Burrell, Christian; Avalon, Nicole E.; Siegel, Jason; Pizzi, Michael; Dutta, Tumpa; Charlesworth, M. Cristine; Freeman, William D.
ABSTRACT: Introduction : Precision medicine provides individualized treatment of diseases through leveraging patient-to-patient variation. Aneurysmal subarachnoid hemorrhage carries tremendous morbidity and mortality with cerebral vasospasm and delayed cerebral ischemia proving devastating and unpredictable. Lack of treatment measures for these conditions could be improved through precision medicine. Areas covered : Discussed are the pathophysiology of CV and DCI, treatment guidelines, and evidence for precision medicine used for prediction and prevention of poor outcomes following aSAH. A PubMed search was performed using keywords cerebral vasospasm or delayed cerebral ischemia and either biomarkers, precision medicine, metabolomics, proteomics, or genomics. Over 200 peer-reviewed articles were evaluated. The studies presented cover biomarkers identified as predictive markers or therapeutic targets following aSAH. Expert commentary : The biomarkers reviewed here correlate with CV, DCI, and neurologic outcomes after aSAH. Though practical use in clinical management of aSAH is not well established, using these biomarkers as predictive tools or therapeutic targets demonstrates the potential of precision medicine.